Creating Art Together as a Transformative Process in Parent-Child Relations: The Therapeutic Aspects of the Joint Painting Procedure - Gavron, Tami; Mayseless, Ofra (Frontiers in Psychology, 2018)
The relationships between parents and children contain implicit aspects, which are nonconscious and nonverbal, in addition to explicit ones. Both explicit and implicit aspects are central to understanding the dyadic dynamics and are implicated in psychotherapy processes and outcomes. Visual symbolization has a unique value as a channel of expression that can capture the implicit characteristics of relationships. Creating art together goes even further because it allows the presence of implicit representations of the relations in vivo. These representations can then be transformed through the joint process of creation, which has a unique potential to unleash reflective capacities when it is experienced in a playful and safe context. This paper presents a qualitative study that is part of larger mixed-methods research with 87 mother-child dyads (with children nine to twelve years old). Dyads were administered the Joint Painting Procedure (JPP), which includes dyadic painting by the parent and child on the same paper and is used for evaluation and treatment in the field of parent-child therapy and art therapy. The study's objectives were to uncover and better understand the unique therapeutic aspects that such method allows and its potential to impact parent-child relationships. The findings of the qualitative study indicated that the JPP enabled several dynamic processes such as pleasure and fun, bi-directionality, mutual regulation, mentalization, and mutual recognition, which together created a salient positive transformation in the relationship. Through the JPP, a new transformative aspect of relations emerges and enables new and different modes of communication and interactions in about half of the dyads and a lesser and partial positive transformation in about a third of them.